2017
DOI: 10.1111/joa.12692
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of snake (Squamata) endocasts: evidence of phylogenetic and ecological signals

Abstract: Brain endocasts obtained from computed tomography (CT) are now widely used in the field of comparative neuroanatomy. They provide an overview of the morphology of the brain and associated tissues located in the cranial cavity. Through anatomical comparisons between species, insights on the senses, the behavior, and the lifestyle can be gained. Although there are many studies dealing with mammal and bird endocasts, those performed on the brain endocasts of squamates are comparatively rare, thus limiting our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 102 publications
(203 reference statements)
6
26
0
Order By: Relevance
“…Plesiosaurian olfactory tracts, elongated anteroposteriorly and not separated along their length (Fig. 3), are similar to those reported in mosasauroids and nothosaurians (Camp, 1942;Voeten et al, 2018) but differ from the short olfactory tracts observed in turtles (Paulina-Carabajal et al, 2013) and the more or less separated olfactory tracts found in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017) and ichthyosaurs (e.g., Marek et al, 2015). Plesiosaurian endocasts are nearly linear (Fig.…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 77%
See 2 more Smart Citations
“…Plesiosaurian olfactory tracts, elongated anteroposteriorly and not separated along their length (Fig. 3), are similar to those reported in mosasauroids and nothosaurians (Camp, 1942;Voeten et al, 2018) but differ from the short olfactory tracts observed in turtles (Paulina-Carabajal et al, 2013) and the more or less separated olfactory tracts found in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017) and ichthyosaurs (e.g., Marek et al, 2015). Plesiosaurian endocasts are nearly linear (Fig.…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 77%
“…3), both the anterior and posterior parts being at the same dorsoventral level, similarly as reported in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017), nothosaurians (Voeten et al, 2018) and turtles (Paulina-Carabajal et al, 2013), a condition differing from that of Placodus gigas (Neenan and Scheyer, 2012), in which the structure appears anteroposteriorly inclined and sigmoidal. The horizontal projection of the plesiosaurian pituitary differs from the tilted one observed in snakes (Allemand et al, 2017c) and thalattosuchians (e.g., Pierce et al, 2017). In plesiosaurians, the cerebellum seems strongly developed and easily discernible (Fig.…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, the addition of earlier aplodontid rodents will be needed to test this hypothesis further. Allemand et al (2017) analyzed the endocranial shape of snakes. Based on their PC analysis, they found that fossorial species had distinct endocranial shapes but arboreal and terrestrial species mostly overlap.…”
Section: Phylogeny and Locomotion In The Squirrelrelated Cladementioning
confidence: 99%
“…water or soil). A resemblance between fossorial and aquatic species has been highlighted previously in snakes at the cranial (Savitzky, 1983) and endocranial level (Allemand et al, 2017), with C. ruffus noticeably grouping with the aquatic species in terms of its endocranial shape. Aquatic and fossorial species share a similar constraint: the high density of the medium in which they live.…”
Section: Discussionmentioning
confidence: 52%